The Role of the Government as a Functionary for Planning and Development in a Region - Putri Kemala Dewi Lubis; Muhammad Nazly Azrai; Avis Raja Satya Purba; Shafdana Mora Ritonga; Samuel Sianturi (LPPM UIKA Bogor, 2024)
The role of local governments in regional development planning is to have the authority and ability to manage and implement regional development programs. Because local governments play a role in determining the success of the process of implementing government activities and regional development. Judging from the policy of the central government to ratify the regional plan document, the community is not satisfied, because the ratification of the regional development plan document by the central government is not based on the plan document submitted to the central government. The purpose of this study is to:) describe and analyze the role of local governments as entrepreneurs, coordinators, facilitators, and stimulators in regional development planning. b) describe and analyze the supporting and inhibiting factors of the role of local government in regional development planning in general. The methods used are; qualitative descriptive, which describes the real situation in the field. The findings in the field are that local governments as entrepreneurs, coordinators, facilitators, and stimulators will involve sectors of each existing ministry to participate in the Regional Development Commission team to verify, evaluate, and supervise priority regional development planning programs.